Parenting practices in early childhood as technologies of power in family and educational contexts (2022)
This research with a post-structuralist epistemological approach and qualitative methodology had the objective of revealing the conditions that make it possible for the parenting practices of caregivers of early childhood children in family and educational contexts to be configured as technologies of power (procedures through which power relations are socially legitimized). Likewise, it was proposed to demonstrate the self-care practices of children configured as technologies of the self. The results made it possible to identify current parenting practices where discipline practices are still evident in both contexts. It is concluded that power relations arise in the middle of a relational triad school - family - childhood, in an apparently functional gear, thus, children are influenced by the processes of both entities and begin to witness how the family has become Foucault's terms in an "institution". Part of the practices carried out by adults are incorporated by children and become self-care practices that, according to the analysis obtained, are part of a powerful formation of technologies of the self, however, not so well achieved. at this age, but a strong constitution is expected in the next stages of the life cycle.